2012
DOI: 10.1371/journal.pone.0034990
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of Malarial Parasites in Orangutans

Abstract: BackgroundRecent findings of Plasmodium in African apes have changed our perspectives on the evolution of malarial parasites in hominids. However, phylogenetic analyses of primate malarias are still missing information from Southeast Asian apes. In this study, we report molecular data for a malaria parasite lineage found in orangutans.Methodology/Principal FindingsWe screened twenty-four blood samples from Pongo pygmaeus (Kalimantan, Indonesia) for Plasmodium parasites by PCR. For all the malaria positive oran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
92
3
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(118 citation statements)
references
References 45 publications
21
92
3
2
Order By: Relevance
“…Group A includes two of the three msp7 paralogs (PVX_082645 and PVX_082695) that have orthologs in all the Plasmodium species considered in this study, including rodents. The phylogenetic relationships within ortholog PVX_082695 inside Group A paralogs clade are similar to those estimated for Plasmodium species using other loci and mtDNA genomes (Muehlenbein et al, 2015; Pacheco et al 2011; Pacheco et al, 2012). Group B, considerably the largest in our phylogenetic analysis (Fig.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Group A includes two of the three msp7 paralogs (PVX_082645 and PVX_082695) that have orthologs in all the Plasmodium species considered in this study, including rodents. The phylogenetic relationships within ortholog PVX_082695 inside Group A paralogs clade are similar to those estimated for Plasmodium species using other loci and mtDNA genomes (Muehlenbein et al, 2015; Pacheco et al 2011; Pacheco et al, 2012). Group B, considerably the largest in our phylogenetic analysis (Fig.…”
Section: Resultssupporting
confidence: 67%
“…1), a species with a recent common ancestor shared with P. vivax, P. cynomolgi, and P. inui. (Muehlenbein et al, 2015; Pacheco et al, 2012). Although 10 paralogs found in P. vivax and P. cynomolgi are shared with P. fieldi , it cannot be ascertained whether all 12 msp7 paralogs are shared and syntenic between the three species due to the lack of genomic information on P. fieldi .…”
Section: Resultsmentioning
confidence: 99%
“…Because the Csp sequences show high polymorphism in the number of repeats in the CR region, only the nonrepetitive regions (5′ and 3′ NR) were used for phylogenetic analyses (20). Results showed that the ape sequences were genetically divergent from the ones circulating in humans and fell outside their haplotype diversity (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…27,82,122 P. coatneyi has been reported as causing natural and experimentally induced disease in a variety of NHP species. However, only cynomolgus macaques (M. fascicularis), 33,34,62,74 pig-tailed macaques (Macaca nemestrina), 62 stump-tailed macaques (Macaca arctoides), 98 and Bornean orangutans (Pongo pygmaeus) 84 have been reported to be susceptible to infection in nature, with or without clinical evidence of disease. In addition to use of those species that are naturally infected, animals in which experimental P. coatneyi infection has been studied to various extents include the rhesus macaque (Macaca mulatta), || black-capped squirrel monkey (Saimiri boliviensis), 109 Japanese macaque (Macaca fuscata), 53,54,56,70 silvery lutung (Presbytis cristalus), 14 and white-handed gibbon (Hylobates lar).…”
Section: Ecology Of Nhp Malariasmentioning
confidence: 99%